Yahoo Web Search

  1. Sort by

  1. yes u can, its called self infliction. they also have a name for "cutters" but i cant think of it. u will know if u have a problem if u cut urself to release any pain that u are...

    5 Answers · Health · 15/07/2007

  2. Let u = v cos(r) v^3 cos^3(r) + 3 v cos(r) = 39 - 3cos(t) Multiply by 4 and...2/3)pi n + (1/3)arccos([ 39 - 3cos(t) ] (3i/2)) Now you know that u = v cos(r) So u = 2i cos[ (2/3)pi n + (1/3)arccos([ 39 - 3cos(t...

    1 Answers · Science & Mathematics · 12/11/2016

  3. ...t know the answer? But anyway this is the way you do it... 277=178-u every time you swap a number to the other side of the '=' (equal) sighn...

    5 Answers · Science & Mathematics · 01/03/2008

  4. Let u=x-2. Then, x=u+2 and dx = du Then, \int 5x/(x-2)^(1/2) dx becomes \int 5(u+2) * u^(-1/2) du= 5\int (u^(1/2)+2 u^(-1/2)) du= 5 (2/3 u^(3/2)+ 4 u^(1...

    3 Answers · Science & Mathematics · 02/08/2006

  5. wow u dont no how to play pool? well first u try to hit a ball in and if its a stiped ball u have to only hit the ...

    4 Answers · Games & Recreation · 09/05/2008

  6. U feel on your face the chilling sensation of the snow that melts. U---ndoubtedly there is no rock on earth that melts. U----...

    21 Answers · Entertainment & Music · 01/12/2006

  7. u play on yahoo mssger is u click the games icon on top of im window and invite them... u have to do it thru the website games and so on. the way u shoot is wit the left click button on mouse u move the stick around...

    1 Answers · Yahoo Products · 19/09/2007

  8. (du/dx)+u+au^(5/4)+u^4 = 0 so (du/dx) = -(u+au^(5/4)+u^4) and thus -du/(u+au^(5/4)+u^4) = dx so we reach the... x(u) to get the desired functional form u(x) Unfortunately, I'm not certain if...

    2 Answers · Science & Mathematics · 19/05/2008

  9. a^u = a^u e^u/e^u a = e^ln(a) a^u = [e^ln(a)]^u a^u = e^[ln(a)*u] ∫a^u du = ∫e^[uln(a)] du Let v = uln(a) --> dv = ln(a) du ∫a^u du = [1/ln(a)]∫e^v dv ∫a^u du = [1/ln(a)] e^v + C ∫a^u du = [1/ln...

    2 Answers · Science & Mathematics · 09/12/2008

  10. u = 1 + x^(1/3) u - 1 = x^(1/3) (u - 1)^3 = x d/du (u - 1)^3 = dx/du 3(u - 1)^2 = dx/du dx = 3(u - 1)^2 du integrate 1 / (1 + x^(1/3)) dx = integrate (1 / u) * (3)(u - 1)^2...

    1 Answers · Education & Reference · 01/12/2013

  1. Try asking your question on Yahoo Answers